Cutaneous Mastocitosis. A singular case - Jorge Luis Valdés González; Urbano Solis Cartas; Elda María Valdés González (Universidad de Ciencias Médicas de La Habana, 2015)
Introduction: the mastocytosis or mastocytoma are a genodermatosis, of unknown etiologic, for which is included in the frequent strange or few groups of illnesses, it generally appears in the childhood or to the moment to be born, it is related with hypersensitivity processes, chronic illnesses or neoplasias. It is characterized by local or systemic accumulation of mast cells, originating cutaneous lesions of different size, persistent, pigmented and very pruriginous. Objective: to give to know the clinical characteristics in a way not very common of presentation of the cutaneous mastocytoma. Case Presentation: the case of a 7 year-old boy is presented with lesions cutaneous characteristics from this illness to which was carried out the diagnosis in the consultation of dermatology of the Alternative Andean Hospital of Chimborazo, Diocese of Riobamba, Ecuador. Conclusions: the cutaneous, although uncommon mastocytosis, presents clinical manifestations that allow to suspect in a beginning its diagnosis, it is of vital importance to discard other chronic illnesses   and/or neoplasias that can be presented in the course of this illness.   Key words: chronic illness, neoplasia, genodermatosis, mastocytoma, mastocytosis, nodules, urticarial.